A Microwave Scattering Model For An Electrically Dense Discrete Random Medium - Ewe , Hong Tat (1999)
This thesis contains a theoretical study of the microwave scattering problems in electrically dense discrete random media and the development of the microwave scattering models with applications to these dense media. A medium is considered electrically dense when the average distance between the scatterers is smaller than the wavelength. In this case, the conventional assumption of independent scattering from the scatterers is no longer valid and the coherence effect from the scatterers should be taken into account. This effect can be included by incorporating the array phase correction factor to the scattering matrix of the scatterers. The array phase correction factor is developed based on the antenna array concept where the overall phase contributions from the correlated scatterers are considered. In this study, the array phase correction factor for spherical scatterers developed by Chuah et.al. ( 1996) is generalized to non -spherical scatteres with either prescribed or random orientation. Theoretical analysis of the array factor for various frequencies, valume fractions and scattering angles is also carried out. In addition to the coherence effect, the near field interaction between the scatterers should also be incorporated in the scattering theory for a dense medium. For spherical scatterers, this near field interaction effect is considered through the amplitude correction where the range dependent terms in the exact expression of the scattered field of Mie scatterers are included. For disks, needles and cylinders, since the overall scattered field of a scatterer is approximated by integrating the scattered fields from each volume element of the scatterer, the near field interaction effect is considered by including not only the near field amplitude term of the scattered fields ( as the amplitude correction ) but also the higher order terms in the phase of the scattered fields ( as the Fresnel phase correction ). For the application of the theoretical model in a dense medium embedded with spherical scatterers such as now, a scattering problem from a single layer of Mie scatterers bounded both on top and bottom by rough interfaces characterized by the IEM model is considered. Theoretical analysis of the model with the amplitude and the array phase corrections is carried out with comparison to the predictions of the dense medium matrix doubling model. In addition, the model predictions are also compared with laboratory and snow field measurement data. Encouraging results are obtained where good agreement with the snow measurement data for co-polarization returns is observed. For cross-polarization returns, more high order terms are found to be necessary for better model predictions. For the study of scattering mechanisms in a vegetation medium, the single layer model is extended to a multilayer model. The leaves, branches and trunks are modelled by simple geometrical shapes such as disks, needles and cylinders. The IEM model is again used to characterize the ground surface. Theoretical studies of the effects of the array phase, the amplitude and the Fresnel phase corrections on the phase matrices of disks, needles and cylinders are presented and good agreement is obtained between the theoretical results and the backscattering cross section measurement of rods, disks, birch stick and aspen leaf. The phase matrices are then applied in the backscatter model and theoretical analysis of the backscattering returns from both the single layer and the multilayer models is carried out. Three types of forests are chosen for the theoretical study of the multilayer model: temperate coniferous forest, tropical deciduous forest and tropical evergreen forest. Various dominat scattering contributions from the vegetation are identified and siscussed. Good agreement is obtained between model predictions and multi-frequency, multi-angle and multi-polarization measurement data for Japanese Cypress, soybean and wheat canopies, boreal forest, walnut orchard and Sugi coniferous trees. In conclusion, it is generally found that the arry phase correction is necessary for an electrically dense medium. In addition, near field interactions such as the amplitude correction and the Fresnel phase correction are also vital in the dense medium models. Good agreement of the model predictions with the available measurement results validates the applicability of the models in this study.